Invertebrate Diversity at Gunung Kidul Beach Yogyakarta as an Effort to Conserve Aquatic Ecosystems (AGARICUS: Advances Agriculture Science & Farming, 2022)
Marine invertebrates are animals that do not have a spine, which live almost throughout the marine water area, but most species of marine invertebrates are numerous in coastal areas such as coral reef areas, This study aims to determine the type of invertebrates, diversity index, aquatic ecosystem conservation efforts. This research was conducted at Krakal Beach and Kukup Beach Gunung Kidul Yogyakarta. Data retrieval is carried out 2 times with a time differentiating system. The method used is a survey method with 3 stations on each beach, the total number of the two beaches is 6 stations. The results of the data collection of invertebrate types found were from the phylum Coelenterata, Arthropods, Mollusca, and Echinodermata. The diversity index on Krakal Beach in the morning is around 1.82 and at noon it is around 1.9 while at Kukup Beach in the morning it is around 1.72 and at noon it is around 1.71 so on both beaches it is still classified as a moderate diversity index, for ecosystem conservation efforts on both beaches are almost the same, namely by cleaning the beach, planting sea pandanus trees and sea cypress trees and establishing POKDARWIS security for the care of animals classified as almost extinct.Keywords: Aquatics, Ecosystems, Invertebrates, Conservation, Krakal and Kukup Beaches